Inverted Echo Sounder Data Near the New England Seamounts 1985-1986 - Hallock, Zachariah R; Teague, William J (1987)
A major component of the field activities for the Northwest Atlantic Regional Energetics Experiment (REX) is focused on collecting and analyzing data from inverted echo sounders (IESs). These instruments provide information concerning the height of the sea surface, as well as information concerning movement of the Gulf Stream and mesoscale features in the REX area. In this report the collection, processing, and preliminary analysis of the IES data and the associated ship expendable bathythermograph and conductivity-temperature- depth data are described, and various plots are presented. These data are generally of good quality and constitute a significant contribution to our understanding of Gulf Stream dynamics. Keywords: Air-launched expendable bathythermographs; Bathythermograph data; Electrical conductivity; Seawater temperature; North Atlantic ocean; Salinity; Seamounts; GEOSAT satellite; Topography; Echo sounders; AXBT probes; Thermocline depth; Moored instrumentation, LORAN.